Mitochondrial dysfunction associated with glucocerebrosidase deficiency - Matthew E. Gegg; Anthony H.V. Schapira (Neurobiology of Disease, 2016)
The lysosomal hydrolase glucocerebrosidase (GCase) is encoded for by the GBA gene. Homozygous GBA mutations cause Gaucher disease (GD), a lysosomal storage disorder. Furthermore, homozygous and heterozygous GBA mutations are numerically the greatest genetic risk factor for developing Parkinson's disease (PD), the second most common neurodegenerative disorder. The loss of GCase activity results in impairment of the autophagy‐lysosome pathway (ALP), which is required for the degradation of macromolecules and damaged organelles. Aberrant protein handling of α-synuclein by the ALP occurs in both GD and PD. α-synuclein is the principle component of Lewy bodies, a defining hallmark of PD. Mitochondrial dysfunction is also observed in both GD and PD. In this review we will describe how mitochondria are affected following loss of GCase activity. The pathogenic mechanisms leading to mitochondria dysfunction will also be discussed, focusing on the likely inhibition of the degradation of mitochondria by the ALP, also termed mitophagy. Other pathogenic cellular processes associated with GBA mutations that might contribute, such as the unfolding of GCase in the endoplasmic reticulum, calcium dysregulation and neuroinflammation will also be described. Impairment of the ALP and mitochondria dysfunction are common pathogenic themes between GD and PD and probably explain why GBA mutations increase the risk of developing PD that is very similar to sporadic forms of the disease.